The Hungarian pear germplasm as source of genetic variability for breeding programmes - Szabó, T.; Labuschagne, I. F.; Musacchi, S.; Nyéki, J.; Tornyai, J.; Soltész, M.; Szabó, Z. (International Journal of Horticultural Science, 2010)
TheHungarian pear collection (Pyrus communis L.) consists of 423 genotypes distributed over seven genebanks inHungary. This is one of themost extensive collections of native and cultivated pears found in Eastern Europe and includes a wide range of genotypes with small size fruit (referred to as “Miniature pears”). Based on the in situ and ex situ measures taken by governmental and other institutions for fruit tree conservation in Hungary, an overview is given on some activities regarding areas of Pyrus collection and genebanks where pears are collected and grown. Descriptions of traits of miniature pears found in Hungarian genebanks for the interest of genetic characterization and breeding are presented.